2015
DOI: 10.4102/aveh.v74i1.22
|View full text |Cite
|
Sign up to set email alerts
|

Comparing visual acuity in preschool children using the Lea symbols and Sheridan Gardiner charts

Abstract: Visual acuity measurement is a vital part of an optometric examination. The purpose of the present study was to compare visual acuity in preschool children using two charts – the Lea symbols chart and the Sheridan Gardiner chart. One hundred and fifty-three preschool children (72 boys and 81 girls) between the ages of 3 and 5 years (mean age and standard deviation 4.23 ± 0.78 years) were recruited from five randomly selected nursery schools. Distance visual acuity was measured monocularly and binocularly after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…As expected, testing time was higher for the youngest 3-year-old group, which could be due to the shorter attention span of younger children. Similar findings in VA score were found in previous Osaiyuwu and Atuanya[ 10 ] Hered et al . had observed that, among the 3 year olds, the cooperation rate was 92% with LS, whereas it was 85% with HOTV chart.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As expected, testing time was higher for the youngest 3-year-old group, which could be due to the shorter attention span of younger children. Similar findings in VA score were found in previous Osaiyuwu and Atuanya[ 10 ] Hered et al . had observed that, among the 3 year olds, the cooperation rate was 92% with LS, whereas it was 85% with HOTV chart.…”
Section: Discussionsupporting
confidence: 91%
“…[ 8 10 15 ] We also observed that the SG tends to overestimate VA scores when compared to LS. Studies done by Simmers et al .,[ 15 ], Schlenker et al .,[ 16 ] and Osaiyuwu and Atuanya[ 10 ] have documented this previously. Osaiyuwu and Atuanya[ 10 ] also commented that this tendency is seen the lower logMAR VA scores.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This is akin to findings of local studies by Obajolowo as well as Osaiyuwu and Atuanya in Nigeria. [ 21 24 ] Hered and Murphy,[ 23 ] in Florida, USA, also reported that VA performance improved with age. This association could be attributed to better cooperation, longer attention span, and a higher level of visual development with age.…”
Section: Discussionmentioning
confidence: 99%